Cooking Class Panna cotta dan Mie dari Pakcoy sebagai Sarana Pemberdayaan Perempuan untuk Mendukung SDG 5 - Binti Azizatun Nafi’ah; Ahmad Bagus Rohim; Laras Ayu Maulida Zahra; Nisa Febriyanti; Rohadatul Sabila; Putri Hana Febrian; Riesa Winanda; Noor Bagas Anggono; Salisyah Salsabilah; Salsabila Puspita Wulandari; Alvien Nosiko (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Pakcoy is a highly nutritious vegetable that has significant health benefits. This community service project aims to promote healthy eating and economic empowerment in Gelam Village by introducing innovative culinary techniques using locally grown pakcoy. Through cooking classes, participants learned to make nutritious and delicious dishes such as panna cotta and noodles using this versatile vegetable. The project successfully engaged local women, fostering a sense of community and providing them with new skills that have the potential to start their own businesses. By diversifying agricultural products and promoting value-added processing, this initiative contributes to sustainable village development and empowers women to play a more active role in the community economy.